Cancer stem cells in sarcomas: Getting to the stemness core - Skoda, Jan; Veselska, Renata (Biochimica et biophysica acta. General subjects, 2018)
BACKGROUND: Sarcomas are rare tumors but represent the third most common malignancy in children. The cancer stem cell (CSC) paradigm is well established, and CSCs have been intensively studied in sarcomas in the past decade. SCOPE OF REVIEW: This review summarizes current knowledge on CSCs in sarcomas and provides new perspectives on the role of a deregulated stemness program in sarcomagenesis. MAJOR CONCLUSIONS: Cell surface markers have so far failed to specifically target sarcoma CSCs. Sarcomas likely arise from immature cells that undergo pathological reprogramming. Transcription factor Sox2, which is frequently upregulated in sarcomas, is directly involved in this process, and its crucial role in the acquisition and maintenance of the CSC phenotype has been demonstrated in various sarcomas. GENERAL SIGNIFICANCE: Sox2 is a core functional regulator of the stem-like state and is an outstanding marker of sarcoma CSCs. Fluorescence protein-based reporters of Sox2 expression might provide useful tools for subsequent studies of sarcoma CSCs.
Keywords: Sarcoma; sarkom; Cancer stem cells; Pluripotency factors; nádorová transformace buněk; Cell Transformation, Neoplastic; Markers; Sox2; SOXB1 Transcription Factors; nádorové kmenové buňky; Animals; lidé; Neoplastic Stem Cells; Mesenchymal stem cells; transkripční faktory SOXB1; Humans; zvířata